Prion diseases - Cohen, Fred (Henry Stewart Talks, 2007)
Understanding the biophysical aspects of a disease of protein misfolding, Structural studies of PrPc and PrPsc, The development of synthetic mammalian prions and the proof of their infectivity and serial transmissibility, Heterocyclic pharmacotherapies for prion disease, Pyridinyl based therapies and structure based design, Serendipitous discovery of acridines as anti-prion agents, Bisacridines as potent inhibitors of prion replication in cell culture, The relationship between the prion diseases and other diseases of protein misfolding
Archived at 2016/04/17